2020
DOI: 10.1007/s10973-020-09543-9
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and dissolution properties of ezetimibe–aspirin binary system in development of fixed-dose combinations

Abstract: The objective of this work was to investigate binary pharmaceutical mixtures of ezetimibe (EZT) and aspirin (ASA) in order to identify whether the occurrence of eutectic in this system has an effect on EZT dissolution improvement. Ezetimibeaspirin (EZT-ASA) solid dispersions prepared by grinding in the whole range of compositions were characterized using differential scanning calorimetry (DSC) for purpose to describe solid-liquid phase equilibrium diagram. The occurrence of interactions between ingredients was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Similar results can be found in the literature [ 32 ]. The spectrum of ezetimibe corresponds with the literature data obtained experimentally [ 29 , 33 ]. The spectrum is characterized by the following bands: 3437.5 and 3275.2 cm −1 (O-H), 2928 cm −1 (C-H); 1730.6 cm −1 (C = O), 1509.7 cm −1 (C = C arom.…”
Section: Resultssupporting
confidence: 67%
“…Similar results can be found in the literature [ 32 ]. The spectrum of ezetimibe corresponds with the literature data obtained experimentally [ 29 , 33 ]. The spectrum is characterized by the following bands: 3437.5 and 3275.2 cm −1 (O-H), 2928 cm −1 (C-H); 1730.6 cm −1 (C = O), 1509.7 cm −1 (C = C arom.…”
Section: Resultssupporting
confidence: 67%
“…After 88 days, an additional 1 H‐ 13 C FSLG HECTOR NMR spectrum with the same resolution in the indirect dimension revealed changes in the 1 H NMR chemical shifts. Górniak et al [ 28 ] and Knapik‐Kowalczuk et al [ 27 ] already showed by DSC that EZI has only one endothermic peak at 164°C, [ 28 ] which corresponds to the melting point, making changes due to elevated temperatures unlikely. A comparison of XRPD powder patterns (Figure 6) of EZI before MAS, which should represent the state of the initial 1 H‐ 13 C FSLG HECTOR NMR spectrum, and after MAS, representing the new spectrum, showed no differences in peak positions, so no completely new phase of EZI has formed.…”
Section: Resultsmentioning
confidence: 99%